2019
DOI: 10.1093/geronb/gbz042
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Before and After Retirement—Assessing the Relevance of Psychosocial Working Conditions: The Whitehall II Prospective Study of British Civil Servants

Abstract: Objectives Retirement could be a stressor or a relief. We stratify according to previous psychosocial working conditions to identify short-term and long-term changes in mental health. Method Using data from the Whitehall II study on British civil servants who retired during follow-up (n = 4,751), we observe mental health (General Health Questionnaire [GHQ] score) on average 8.2 times per participant, spanning up 37 years. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 50 publications
(92 reference statements)
3
46
1
Order By: Relevance
“…This is in line with a review concluding that retirement has beneficial effects on mental health 3, and other studies observing decreasing depressive symptoms in relation to retirement (14). Our results were also in line with those by Fleischmann et al (16), which showed that mental health improves already before retirement. However, we adopted a different analytic strategy than many previous studies on this topic and supported a heterogenous development of depressive symptoms across retirement (11,12).…”
Section: Main Findingssupporting
confidence: 94%
See 2 more Smart Citations
“…This is in line with a review concluding that retirement has beneficial effects on mental health 3, and other studies observing decreasing depressive symptoms in relation to retirement (14). Our results were also in line with those by Fleischmann et al (16), which showed that mental health improves already before retirement. However, we adopted a different analytic strategy than many previous studies on this topic and supported a heterogenous development of depressive symptoms across retirement (11,12).…”
Section: Main Findingssupporting
confidence: 94%
“…The fact that most of the psychosocial working characteristics were associated with a higher probability of belonging to the moderate depression, considerably decreasing (group 3) trajectory, may indicate that the retirement-related relief from exposure to these work stressors could have a beneficial effect on depressive symptoms. Fleischmann et al (16) also found support for such a relief where positive changes in mental health were more explicit for those retiring from poorer working conditions including high job demands, lower social support, or lower decision authority. This was in line with our findings except for the results regarding decision authority.…”
Section: Main Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the results of the French study were based on a different analytical approach from ours as they reported average changes in suboptimal health before and after retirement in prespecified groups, and our analyses were based on latent trajectory analyses. Previous studies have reported that transition to retirement associates with an improvement in mental health,8 10 increase in physical activity,30 as well as decrease in sleep difficulties16 31 and in BMI,20 which may partly mediate the improved health perception after retirement especially among those with higher occupational status.…”
Section: Discussionmentioning
confidence: 96%
“…Retirement is a life transition in late adulthood accompanied by removal of work-related activities, roles and stressors, as well as reduced income and increase in time availability and flexibility. An increasing number of studies have examined the effect of retirement on physical and mental health, but the results have been inconsistent,1 with some studies suggesting improved perceived general health2–5 and mental health,6–10 while other studies have found negative or no changes in health after retirement 9 11 12…”
Section: Introductionmentioning
confidence: 99%